The current role for clinical and renal histological findings as predictor for outcome in Australian patients with lupus nephritis - Nossent, J.; Raymond, W.; Kang, A.; Wong, D.; Ognjenovic, M.; Chakera, Aron (2018)
© The Author(s) 2018. Objectives: To investigate the current demographic, clinical and histological characteristics of patients with lupus nephritis (LN) in Western Australia (WA) with regards to their predictive value for patient and renal outcome. Methods: Retrospective study of adult systemic lupus erythematosus (SLE) patients with a first renal biopsy demonstrating LN between 1997 and 2017 at a metropolitan tertiary hospital in WA. Clinical data were collected at baseline and last follow-up with renal biopsy findings classified by International Society of Nephrology (ISN) criteria. Annual incidence rates (AIRs)/100,000, Kaplan–Meyer curves and Cox regression hazard ratio for independent predictors for patient and renal survival were applied. Results: The AIR was 3.3, 3.1 and 0.4 for Asian (n = 29), Indigenous Australian (IA) (n = 11) and Caucasian (n = 43) patients, respectively (p < 0.01). There was no significant subgroup difference regarding ISN class (proliferative 66%, membranous 19%, mesangial 15%), levels of proteinuria (median PCR 300 mg/mmol) or frequency of raised creatinine (31%), anti-dsDNA antibody (89%) or hypocomplementaemia (88%). Treatment included corticosteroids (91%), cyclophosphamide (30%), mycophenolate (67%) and antihypertensive drugs (67%). Five- (81%) and 10-year (70%) survival was lower for IAs than for Caucasians and Asians (95% each at both time points) (p = 0.016). Five- and 10-year renal survival (endpoint renal replacement therapy (RRT)) was 86% and 64% for IA vs 100% for Asian, 100% and 96% for Caucasian patients (p = 0.02). IA background was the only independent predictor for poor patient survival and together with male gender also for renal survival. Only 25% of all patients remained free of any organ damage with non-renal damage observed in 53% of survivors. Conclusions: LN incidence in WA was 0.75/100,000 with the lowest rate observed in Caucasians. While Asian patients have the same favourable outlook as Caucasians, the outcome is much bleaker for IA patients. Other clinical and histological findings did not predict outcomes, and importantly more than half of all surviving patients accrued non-renal damage.